Modeling the effects of flow dispersion in arterial spin labeling. - Kazan, S; Chappell, M; Payne, S (2009)
Recent experimental results have shown that effects such as dispersion and cardiac pulsation have a significant effect on the arterial spin labeling (ASL) signal. These have not been incorporated into the existing ASL models potentially leading to inaccuracies in flow calculation. In this study, we develop a new model, based on physical principles, to model the transit of the ASL signal from the tagging band to the imaging band using the mass transport equation. We relax the assumption of a uniform plug flow, and account for the dispersion caused by the viscous nature of blood. The model also provides a framework within which other physiological aspects can easily be examined. Here, we examine the effects of flow dispersion on the ASL signal, and hence the quantification of cerebral perfusion. Our results suggest that not accounting for flow dispersion may result in inaccurate values of cerebral perfusion.